10th Euro Fed Lipid Congress: From science and technology to health (Cracow, 23–26 Sep 2012). Issue 2 (12th February 2013) - Unknown
Abstract Six hundred scientists from around the globe participated in the 10th Euro Fed Lipid Congress, which was held from September 23rd to 26th, 2012 in Cracow, Poland. Cracow, which was Poland's capital from the 11th to the 16th century, has a beautiful old town with many sights and is visited by over 7 million tourists every year. The Congress venue was Auditorium Maximum of the Jagiellonian University – one of the oldest universities in the world, established in 1364. The Congress was opened on Sunday with plenary lectures followed by the welcome reception and table top exhibition – a perfect opportunity for networking and informal discussions. Every day started with a plenary lecture, and continued with three blocks of topical sessions, one in the morning and two in the afternoon, and poster viewing sessions in the evening. The lecture and poster abstracts are available online 1. In this Meeting Report, the chairmen and chairwomen present the highlights of the oral presentations given during the sessions. For more information on past and future EuroFedLipid meetings and congresses, please visit http://www.eurofedlipid.org.